2008
DOI: 10.1002/jsfa.3395
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced preservation effects of sugar apple fruits by salicylic acid treatment during post‐harvest storage

Abstract: BACKGROUND: Salicylic acid (SA) is recognised as an endogenous signal, mediating in plant defense and against pathogens. It has been reported that SA treatment can reduce decay and extend storage life of various fruit, such as bananas, peaches and apples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
70
1
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(91 citation statements)
references
References 32 publications
12
70
1
8
Order By: Relevance
“…The findings of Ding and Wang [29] confirmed that SA has the ability to reduce ethylene production [32] and delay ripening. A similar observation has been reported in kiwi dipped in ASA at 1000 µmol l -1 for 5 min [33,34], in strawberries, treated with SA at 1000-4000 µmol l -1 [35], in custard apples dipped in SA at 400, 800 and 1200 µmol l -1 for 15 min [25]. It has been reported [29,33] that treatment with ASA suppresses the activity of ACC (aminocyclopropanecarboxylate) oxidase and ACC synthase, reducing conversion of ACC to ethylene.…”
Section: Physiological Effects Respirationsupporting
confidence: 76%
See 4 more Smart Citations
“…The findings of Ding and Wang [29] confirmed that SA has the ability to reduce ethylene production [32] and delay ripening. A similar observation has been reported in kiwi dipped in ASA at 1000 µmol l -1 for 5 min [33,34], in strawberries, treated with SA at 1000-4000 µmol l -1 [35], in custard apples dipped in SA at 400, 800 and 1200 µmol l -1 for 15 min [25]. It has been reported [29,33] that treatment with ASA suppresses the activity of ACC (aminocyclopropanecarboxylate) oxidase and ACC synthase, reducing conversion of ACC to ethylene.…”
Section: Physiological Effects Respirationsupporting
confidence: 76%
“…Reduced respiration rate was also observed in pomegranates dipped in acetyl salicylic acid (ASA -a close analogue of salicylic acid) at 100, 500 and 1000 µmol l -1 for 10 min, stored at 2 °C [13]. The positive effects were associated with either reduced chilling injury in MeJA treated loquat [16], SA treated plums [24] and pomegranates [13] or delayed ripening observed in SA treated banana [23] and custard apples [25].…”
Section: Physiological Effects Respirationmentioning
confidence: 95%
See 3 more Smart Citations